Pertumbuhan Bakteri Photorhabdus luminescens pada Berbagai Media dan Produksi Eksotoksin sebagai Racun Serangga - Wartono Wartono; Tri Puji Priatno (Jurnal Entomologi Indonesia, 2009)
The aim of this experiment was to find out the type of medium that was potential for the metabolite production and growth of P. luminescens. LB, NB, Wakimoto, and T3 were examined as growth media for metabolite production and growth of P. luminescens. LB was the best medium for the growth of P. luminescens and metabolite production.